Pengaruh Metode Latihan dan Motivasi Berlatih Terhadap Keterampilan Bermain Sepak Bola Pada Pemain SSB PSP Bangko: (The Effect of Training Methods and Motivation on Practicing Against Football Skills on PSP Bangko SSB Players) - Andrew Sonawijaya; Sayuti Syahara; Damrah Damrah (Jurusan Pendidikan Olah Raga dan Kepelatihan FKIP Universitas Jambi, 2020)
This study aims to look at the effect of global training methods, elementary training methods, and motivation to practice on soccer playing skills. The type of research used is a quasi-experimental. Motivational instrument practice is measured by using a soccer skill test consisting of four forms of tests namely dribbling, short passed, shooting at the goal, and ball control. The data obtained were then analyzed by analysis of two-way variance (ANAVA) and continued with the Turkey test. Based on the research findings, it can be concluded that (1). Global training methods are better used to improve the skills to play football. PSP Bangko (A1) SSB players = 63.75 are better, than Elementary (A2) training methods = 61.25, (2). High motivation groups have the skills to play football (B1) = 63.57 better than the low motivation group (B2) = 61.41, (3). There is an interaction between the training method and the motivation to practice the pregnancy playing football in the PSP Bangko SSB player, (4). In the PSP Bangko SSB players the high training motivation (A1B1) = 68.31 was better than the Elementary training method group (A2B1) = 58.86, and (5). In the PSP Bangko SSB players the low training motivation level (A2B2) = 63.63 was better than the Global training method (A1B2) = 59.19 to improve the playing skills of SSB PSP Bangko football players.